The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1740-0929.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

A cell wall preparation of Enterococcus faecalis strain EC‐12 stimulates β‐defensin expression in newly hatched broiler chicks

Abstract: In our previous study, a cell wall preparation of Enterococcus faecalis strain EC‐12 (EC‐12) prevented the colonization of vancomycin‐resistant enterococci (VRE) in newly hatched broiler chicks. Relatively early prevention against VRE colonization by EC‐12 administration may be related to the enhanced innate immune system. In this study we examined the effect of EC‐12 on the kinetics of immunoglobulin A (IgA) concentration in the cecal digesta of chicks from 1 day to 14 days old to evaluate humoral immunity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…were more resistant to the pathogenic effects of coliform. The antimicrobial effects of probiotics come from the volatile fatty acid and other organic acids such as lactate and succinate (Kubena et al, 2001) and through the production of bacteriocins and phage-displayed peptides (Sakai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…were more resistant to the pathogenic effects of coliform. The antimicrobial effects of probiotics come from the volatile fatty acid and other organic acids such as lactate and succinate (Kubena et al, 2001) and through the production of bacteriocins and phage-displayed peptides (Sakai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Dead probiotics, on the other hand, are proven as good a biological immune modifier as viable probiotics (Sakai et al . , ; Chuang et al . ) and, moreover, are safer with longer shelf‐life (Adams ).…”
Section: Introductionmentioning
confidence: 99%
“…Dead probiotics, on the other hand, are proven as good a biological immune modifier as viable probiotics (Sakai et al 2006(Sakai et al , 2007Chuang et al 2007) and, moreover, are safer with longer shelf-life (Adams 2010). Due to the existence of pre-gastric fermentative rumen, dietary supplementation of probiotics to cattle is relatively less common.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that a cell preparation of Enterococcus faecalis strain EC‐12 (EC‐12) stimulated the immune functions in rodents (Kuramoto et al . 2004), chicks (Sakai et al . 2006, 2007) and pigs (T. Tsushima et al .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, most of the immune stimulation by LAB is supposed to be derived by their cell wall preparations (Meydani & Ha 2000), and thus dead LAB cells may also have an immunostimulatory effect in juvenile calves. We previously demonstrated that a cell preparation of Enterococcus faecalis strain EC-12 (EC-12) stimulated the immune functions in rodents (Kuramoto et al 2004), chicks (Sakai et al 2006(Sakai et al , 2007 and pigs (T. Tsushima et al unpubl. data, 2007).…”
Section: Introductionmentioning
confidence: 99%